Factors of Organophosphate Pesticide Exposure on School Children in An Agricultural Area, Indonesia (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Organophosphate is widely used in agriculture in Indonesia and contributes to a public health problem. However, the risk factors of organophosphate exposure, particularly in children living in the agricultural area, have not been described. The research aimed to assess the risk factors associated with organophosphate pesticide exposure on school children living in the agricultural area. This work was a cross-sectional study in 2017 with 166 school children were selected by simple random sampling. Structured questionnaires identified risk factors. Organophosphate metabolites detected by using LC-MS/MS. While chi-square and binary logistic tests as statistical analysis (Î±=0.05; 95%CI). In 28.9% of subjects, organophosphate metabolites were detected. Cut the onion leaves (p=0.002, OR=3.33, 95% CI:1.55âˆ’7.15), the onion, pesticide equipment, or pesticide in their neighbors (p=0.007; OR=2.67; 95%CI:1.31âˆ’5.46) was associated with organophosphate pesticide exposure. Involvement in agriculture activities and the onion, pesticide equipment, or pesticide in the neighbor.